Early transcriptomic response of the mycoparasite Sphaerodes mycoparasitica to the mycotoxigenic Fusarium graminearum 3-ADON, the cause of Fusarium head blight - Seon Hwa Kim; Vladimir Vujanovic (Bioresources and Bioprocessing, 2021)
Abstract Mycoparasites are an assemblage of biotrophic and necrotrophic fungi that occur on plant pathogenic fungal hosts. Biotrophic mycoparasites are often overlooked in transcriptomic-based biocontrol studies. Sphaerodes mycoparasitica (S.m.) is a specific biotrophic mycoparasite of plant pathogenic Fusarium graminearum (F.g.), a devastating Fusarium head blight (FHB) disease in small-grain cereals. To understand the biotrophic mycoparasitism comprehensively, we performed Illumina RNA-Seq transcriptomic study on the fungus–fungus interaction in vitro. The aim is to identify the transcript-level mechanism related to the biotrophic S.m. mycoparasitism, particularly its ability to effectively control the F.g. 3-ADON chemotype. A shift in the transcriptomic profile of the mycoparasite was triggered in response to its interaction with F.g. during recognition (1.5 days) and colonization (3.5 days) steps. RNA-Seq analysis revealed ~ 30% of annotated transcripts with "function unknown". Further, 14 differentially expressed genes functionally linked to the biotrophic mycoparasitism were validated by quantitative real-time PCR (qPCR). The gene expression patterns of the filamentous haemagglutinin/adhesin/attachment factor as well as cell wall-degrading glucanases and chitinases were upregulated by host interaction. Besides, mycoparasitism-associated antioxidant resistance genes encoding ATP-binding cassette (ABC) transporter(s) and glutathione synthetase(s) were upregulated. However, the thioredoxin reductase was downregulated which infers that this antioxidant gene can be used as a resistance marker to assess S.m. antifungal and antimycotoxigenic activities. The interactive transcriptome of S. mycoparasitica provides new insights into specific mycoparasitism and will contribute to future research in controlling FHB. Graphic Abstract